(untitled) (Jurnal Bahasa, 2004)
This study attempts to evaluate how poetry can be very effective when its discourse is characterized by appropriate grammatical structures. In this study, focus will be made on linguistic and semantic structures of Baha Zain’s poems which will be analyzed in accordance with the contribution of grammatical structures to the development of their appropriate meanings and relevant interpretations. The idea of this study is to deal with poets treatment of grammatical texture in his poems. In poetry, a difference in grammatical concepts does not necessarily represent a difference in the meaning referred to it. Such difference will be the evidence of semantic interpretation of the words used in poetry, as is evident in a few of Baha Zain’s poems. Further analysis will be made to insist on the role played by semantic rules over the structural propositions envisaged in the poem. Further possibility will be looked upon the role played by the "figure of grammar" in Baha’s poetry which is not arbitrary in linguistic description but fully functional in the structure of poetry at the heart of metalanguage. This is where the truth of language expressions may not be realized as the same reality in metalanguage. Interpretation will be shown to play a great deal in the making of translated realities of the artwork of Baha Zain. All these will be clearly shown in this study with certain concepts like reference and sense are shown to differ in an effort to construe the image and contents of the message of Baha’s poems. Terms in semantics like metaphor, metonymy, interpretive abduction and inter-lexical relations etc. will be used as devices to generalize the various different meanings underlying the surface structures of the poetic discourse. As a whole, a conclusion will be made as to how grammatical structures becomes clues for creating good and clear perceptions over the meaning intended by the poet as well as his philosophy as intelligibly perceived by the message of his poems being studied. In this study, the writer uses the concepts of grammatical structures and categories as are used in the Theory of Minimalist Grammar.